2017
DOI: 10.1021/acs.jpcc.7b07073
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Computational Study of Ion Association in the Electroreduction of PW12O403–

Abstract: Insights into ion pairing effects on the redox properties of the Keggin-type polyoxotungstate PW12O40 3are gained by combining electrochemical experiments and density functional theory (DFT) calculations. Such effects have been reported to affect the performance of these species as molecular electrocatalysts.Experimental square wave voltammetry (SWV) of the two-electron reduction of PW12O40 3in acetonitrile evidences that the reduced forms PW12O40 4and PW12O40 5can be significantly stabilized by ion associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 79 publications
1
18
0
Order By: Relevance
“…Similarly, in CH 2 Cl 2 /TBAPF 6 , ion pairing between KuQ 3 · – and supporting electrolyte cations occurs, thus inhibiting reversibility. 22 , 23 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, in CH 2 Cl 2 /TBAPF 6 , ion pairing between KuQ 3 · – and supporting electrolyte cations occurs, thus inhibiting reversibility. 22 , 23 …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, in CH 2 Cl 2 /TBAPF 6 , ion pairing between KuQ 3•− and supporting electrolyte cations occurs, thus inhibiting reversibility. 22,23 Therefore, tetrabutylammonium perchlorate (TBAP) has been chosen as the supporting electrolyte for further experiments. Previous works demonstrated that solvent polarity affects the acid−base equilibrium in KuQs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work had demonstrated that the presence of different cations can lead to signicant shis of the redoxprocesses in polyoxometalates. 29,50 To explore this behaviour for {Ca 2 V 12 }, we performed cyclic voltammetry using deaerated, anhydrous DMF containing LiPF 6 (0.1 M) as the electrolyte (see the ESI, Fig. S11 †).…”
Section: Electrochemical and Spectro-electrochemical Analysismentioning
confidence: 99%
“…In particular, in recent years, the solventand ion-related effects on polyelectrolytes have drawn significant interest. Previous atomistic MD simulations, for example, showed that the behavior of molecular solving greatly influences the sum of dissociated counterions and hence the resulting conformational behaviour of repulsive electrostatic interactions or charge screening effects along the polyelectrolyte backbone [9,14,15]. The presence of the polyelectrolyte as expressed by local dielectric constant changes, asymmetry effects of charge hydration, or modified charge transfer mechanisms [16][17][18], affects the molecular structure of the solvent molecules.…”
Section: Introductionmentioning
confidence: 99%